2009
DOI: 10.1038/hr.2008.35
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in elevated blood pressure induced by high free fatty acids

Abstract: The aim of the study is to investigate the possible mechanism of oxidative stress in the high free fatty acids (FFAs)-induced hypertension. Male Sprague-Dawley rat models were established and classified into three groups, namely the control group (NC group), the FFA group, and the N-acetylcysteine (NAC) group. Blood pressure (BP) was recorded. An organ chamber experiment was performed to determine endothelium-dependent/-independent vasodilation (EDV/EIV). Reactive oxygen species (ROS), nitrotyrosine, reduced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Most studies have linked fat and oxidative stress 4446 . Animal and human fat have been shown to increase free radical production 47, 48 . This contributes to increased oxidative stress in the vascular wall, endothelial dysfunction and hypertension 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have linked fat and oxidative stress 4446 . Animal and human fat have been shown to increase free radical production 47, 48 . This contributes to increased oxidative stress in the vascular wall, endothelial dysfunction and hypertension 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have confirmed that hypertension is related to oxidative stress, which could contribute to endothelial dysfunction, leading to elevated BP. 22 Further studies are needed to evaluate the mechanism of this association.…”
Section: Serum Ferritin Tibc and 4-year Incidence Of Hypertensionmentioning
confidence: 97%
“…Potential adverse metabolic consequences of lipotoxicity (55) include abnormalities of glucose and lipid metabolism (5,56), and high blood pressure (57).…”
Section: Free Fatty Acids and Lipotoxicitymentioning
confidence: 99%